2015
DOI: 10.1123/japa.2012-0313
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Physical and Cognitive Exercise Improves Reaction Time in Persons 61–84 Years Old

Abstract: We have compared the effects of different 12-week exercise programs on simple and choice reaction and movement times in persons 61 to 84 years old. One hundred thirty-eight volunteers were randomized to either a control group, a two-day exercise group (two 60-min sessions a week of aerobic exercises), or a two-day physical plus cognitive exercise group (two 60-min sessions a week of aerobic and cognitive exercises). At follow-up, the aerobic and cognitive exercise program was found to have resulted in signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 39 publications
1
50
0
2
Order By: Relevance
“…Simultaneous exercise and cognitive interventions have been shown to have positive influences on cognition in older adults with a variety of exercise activities yielding similar results [ 11 , 22 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Meta-analyses comparing combined interventions to mental-only and physical-only interventions indicated that the combined intervention is more effective than the individual components [ 50 , 73 , 74 ].…”
Section: Introductionmentioning
confidence: 87%
“…Simultaneous exercise and cognitive interventions have been shown to have positive influences on cognition in older adults with a variety of exercise activities yielding similar results [ 11 , 22 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Meta-analyses comparing combined interventions to mental-only and physical-only interventions indicated that the combined intervention is more effective than the individual components [ 50 , 73 , 74 ].…”
Section: Introductionmentioning
confidence: 87%
“…However, there is some evidence that simultaneous exercise-cognitive training studies incorporating aerobic training combined with cognitive challenges (e.g., exergaming) and memory training, are associated with cognitive improvements in healthy older adults (Anderson-Hanley et al, 2012 ; Theill et al, 2013 ; Barcelos et al, 2015 ). In addition, studies that have incorporated PRT with balance training (Hiyamizu et al, 2012 ), stepping exercises (Kayama et al, 2014 ; Nishiguchi et al, 2015 ), and/or aerobic training (Leon et al, 2015 ; Yokoyama et al, 2015 ), performed with secondary cognitive or motor tasks, have also shown positive effects on cognition (Table 2 ). For example, improvements in executive function, global cognitive function and attention were observed in community dwelling older adults following 12-weeks of low-intensity aerobic and PRT performed simultaneously with arithmetic and word games, compared to an exercise-only (60-min three times a week) group (Yokoyama et al, 2015 ).…”
Section: Effects Of Simultaneous Exercise-cognitive Training On Cognimentioning
confidence: 99%
“…However, a limitation of many of the current simultaneous training interventions is a lack of a factorial 2 × 2 design, which makes it difficult to determine whether simultaneous exercise-cognitive programs can provide added cognitive benefits to exercise or cognitive training alone. Nonetheless, 12-weeks of a multimodal exercise program incorporating aerobic training and PRT (60-min twice per week) performed in conjunction with motor tasks (e.g., walking, object manipulation) regulated by external cues, improved choice reaction time in community-dwelling older adults, compared to a group that performed exercise only, and a usual care group (Leon et al, 2015 ). While further long-term, well-designed factorial RCTs are needed, the available data indicates that multimodal exercise programs performed under dual-task conditions provide more consistent cognitive benefits in older adults.…”
Section: Effects Of Simultaneous Exercise-cognitive Training On Cognimentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has found that the combination of both cognitive and physical exercises significantly increased reaction time in elderly populations [15]. This suggests that the mind and body are connected through multiple facets.…”
Section: Reaction and Activity Response Timementioning
confidence: 99%